Patient and Caregiver Agreement on Prognosis Estimates for Older Adults with Advanced Cancer - Loh, Kah Poh (Cancer, 2020)
BACKGROUND: Disagreement between patient and caregiver about treatment benefits, care decisions, and patient’s health is associated with increased patient depression as well as increased caregiver anxiety, distress, depression, and burden. Understanding factors associated with disagreement may inform interventions to improve the aforementioned outcomes. METHODS: This analysis utilized baseline data from a cluster-randomized geriatric assessment trial that recruited patients aged ≥70 with incurable cancer from community oncology practices (URCC 13070; PI: Mohile). Patients and caregivers were asked to estimate the patient’s prognosis. Response options were 0–6 months, 7–12 months, 1–2 years, 2–5 years, and >5 years. The dependent variable was categorized into exact agreement (reference), patient reported a longer estimate, or caregiver reported a longer estimate. We used generalized estimating equations with multinomial distribution to examine factors associated with patient-caregiver prognostic estimates. We selected independent variables using purposeful selection method. RESULTS: Among 354 dyads (89% patients screened were enrolled), 26% and 22% of patients and caregivers, respectively, reported a longer estimate. Compared to dyads in agreement, patients were more likely to report a longer estimate when patients screened positive for polypharmacy (β=0.81, P=0.001) and caregivers reported greater distress (β=0.12, P=0.03). Compared to dyads in agreement, caregivers were more likely to report a longer estimate when patients screened positive for polypharmacy (β=0.82, P=0.005) and had lower perceived self-efficacy in interacting with physicians (β=−0.10, P=0.008). CONCLUSION: Several patient and caregiver factors were associated with patient-caregiver disagreement about prognostic estimates. Future studies should examine the effects of prognostic disagreement on patient/caregiver outcomes.